Discovery of novel isoflavone derivatives as AChE/BuChE dual-targeted inhibitors: synthesis, biological evaluation and molecular modelling - Bo Feng; Xinpeng Li; Jie Xia; Song Wu (Taylor & Francis Group, 2017)
AChE and BuChE are druggable targets for the discovery of anti-Alzheimer's disease drugs, while dual-inhibition of these two targets seems to be more effective. In this study, we synthesised a series of novel isoflavone derivatives based on our hit compound G from in silico high-throughput screening and then tested their activities by in vitro AChE and BuChE bioassays. Most of the isoflavone derivatives displayed moderate inhibition against both AChE and BuChE. Among them, compound 16 was identified as a potent AChE/BuChE dual-targeted inhibitor (IC50: 4.60 μM for AChE; 5.92 μM for BuChE). Molecular modelling study indicated compound 16 may possess better pharmacokinetic properties, e.g. absorption, blood-brain barrier penetration and CYP2D6 binding. Taken together, our study has identified compound 16 as an excellent lead compound for the treatment of Alzheimer's disease.